The effect of plywood thickness on profile steel sheeting dry board (PSSDB) floor panel with foam concrete in-fill - Fatin Nur Amni, Aminuddin (2015)
Rapid growth and development in the construction industry has resulted in increasing demands for an effective and innovative construction systems and techniques. Construction normally will involve commonly using materials such as reinforced concrete and other similar industrialize building systems (IBS) that are more acceptable. The Profiled Steel Sheeting Dry Board (PSSDB) is a light composite system, thin walled that consisted of profile steel sheeting connected to dry-board with self-drilling and self-tapping connectors. The PSSDB floor panel system carried out the shear and plane bending as the function of the floor is to safely support all the possible vertical loads, and then transfer the load to the foundation via members supporting the floor. The scope of this study is to determine the behaviour of in-filled mixture in Profile Steel Sheeting on the PSSDB floor panel. In this experiment, the bending test will be carried out by using the compression and flexural test machine (Magnus Frame & Apparatus 30 Tonne). This procedure will use different size of plywood, which are 3 mm, 4 mm and 6 mm each. The screws type that used to attach the steel sheeting and dry board are MKFastener. Based on the bending experiment, the stiffness of the panel can be determined by calculating the slope for each graph of Load vs Deflection that has been obtained. The results of the stiffness are increased from 180 kNm2/m to 184 kNm2/m when the thickness of plywood is increased from 3mm to 6mm. According to the result obtained, it showed that the increasing thickness in plywood will give the increasing in stiffness. However, in this experiment, the foam concrete will be used as a filling. So, Foam concrete help to decrease deflection of floor compare to non filled profile steel sheeting dry board and increase the stiffness. In other words, thicker plywood will give the stronger floor panel compare to the thin plywood.